A modified yeast three-hybrid system enabling both positive and negative selections - Wallis, C.P.; Filipovska, A.; Rackham, Oliver (SPRINGER, 2018)
Objective: To increase the reporter repertoire of the yeast three-hybrid system and introduce the option of negative selection. Results: Two new versions of the yeast three-hybrid system were made by modifying the MS2 coat RNA-binding protein and fusing it to the Gal4 DNA-binding protein. This allows the use of Gal4 inducible reporters to measure RNA–protein interactions. We introduced two mutations, V29I and N55K into the tandem MS2 dimer and an 11 amino acid deletion to increase RNA–protein affinity and inhibit capsid formation. Introduction of these constructs into the yeast strains MaV204K and PJ69-2A (which contain more reporters than the conventional yeast three-hybrid strains L40-coat and YBZ-1) allows RNA–protein binding interactions with a wide range of affinities to be detected using histidine auxotrophy, and negative selection with 5-fluoroorotic acid. Conclusion: This yeast three-hybrid system has advantages over previous versions as demonstrated by the increased dynamic range of detectable binding interactions using yeast survival assays and colony forming assays with multiple reporters using known RNA–protein interactions.